Karya I Ketut Budiana Menjadi Sumber Inspirasi Karya Seni Lukis - Ega Arsana, I Wayan; Supriyatini, Sri; Karja, I Wayan (Program Studi Seni Murni ISI Bali, 2022)
Departing from an idea about the author's past which always has its own meaning in every strange form, which raises the theme of I Ketut Budiana's Painting As a Source of Painting Inspiration. departing from an idea about the author's past which always has its meaning in every strange form. From this the urge to present visualizations of human figures and creatures in nature by combining certain techniques and references to achieve the desired goals and meanings. The problem presented is how to process the form and represent ideas so that in realizing the work looks interesting. The goals and benefits are to reflect the new and elevate the existing existence. To answer what is the purpose of this work, the method of creation uses exploration, improvisation, and formation. With elements of art, and through the stages of exploration, improvisation, and the formation stage, and combined with ideas and ideas to create 6 works entitled: 1) “Becoming a Slave”, 2) “Forgot Time”, 3) “Bird”, 4) “Where to?”, 5) “Ghost!!!”, 6) “Training”. In the end, it can be said that traditional art, which inspires a lot of work and is very interesting to be raised and developed with imaginative ideas, will become worthy and meaningful works. With the creation of this work, it is hoped that it can convey a message or meaning to a personal phenomenon that the author has experienced.